Material didáctico para lograr fluidez en la lectura en niños de segundo año de Educación General Básica, de la Unidad Educativa ciudad de Alausí, durante la emergencia sanitaria covid-19, para el año lectivo 2020 -2021. - Ordóñez Sanmartin, Sonia Yolanda (2021)
The subject of this research is “Didactic material to achieve reading fluency in children in the Second Year of Basic General Education, during the covid-19 health emergency, for the 2020 -2021 school year. One of the main characteristics that motivated this research to be carried out was the search to improve the teachinglearning process. That due to the pandemic that Ecuador is going through, the classes are being held through the virtual platform ZOOM, where didactic material was created for the teaching of literacy, the classes were dynamic so that the children did not get bored and thus They could assimilate the knowledge, for which each didactic material that was developed was easy to develop, with recycled materials and according to the theme that was planned for each class. In carrying out this research, 1 teacher and 28 students took part, in addition, certain didactic methodologies were used for the development of literacy in girls and boys. This research has a qualitative-quantitative methodology, with a socio-educational modality, descriptive level and a type of bibliographic and field research; The technique used to collect the information was a survey, the same that was applied to 5 teachers of the institution, which helped to know if they use didactic material during the virtual class hours, in order to later tabulate and in this way perform the analysis and interpretation of results. The central objective of this research is to develop a proposal for didactic material to achieve fluency in reading in children of Second EGB, during the COVID-19 health emergency, a design proposal that seeks to cover all the needs and demands of literacy in children . We worked with the projects according to the planning of the Ministry of Education, in what refers to the teaching of literacy, adapting according to the needs of the students and thus achieving a more meaningful teaching in the girls and boys. Keywords: didactic material, literacy, teaching-learning